METHODOLOGY OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE IN THE NATIONAL RUSSIAN SCHOOL - Rakhmanova G. G. (Bright Mind Publishing, 2025)
The article examines current issues in the methodology of teaching Russian as a non-native language in school education.
Keywords: Methodology, teaching, language system, means of communication, speech, communicative skills and abilities, linguistics.